2012
DOI: 10.1016/j.apgeochem.2012.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of landfill leachate through compacted natural clays containing small amounts of carbonates and sulfates

Abstract: Diffusion of a synthetic urban landfill leachate through compacted natural illitic clays and the role of reactive accessory minerals (carbonates and gypsum) in the geochemical behavior of major soluble ions are evaluated. The leachate is composed of NH þ 4 and Na + (0.25 M) balanced by Cl À (0.25 M), acetate (0.1 M) and HCO À 3 (0.15 M). The pH is 7.8 and it is typical of the mature stage of organic matter degradation within an urban landfill. Laboratory scale diffusion tests were performed over 4 months (long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
1
7
0
3
Order By: Relevance
“…Studies that focused on very low solid-water ratios (Nakashima et al, 1999), that used high concentrations of the diffusing species (Nakashima, 2002(Nakashima, , 2003bLoomer et al, 2013), or that studied the codiffusion of multiple species (De Soto et al, 2012) were excluded, as were data obtained with bentonites other than Na þ -, Ca 2þ -, or Na þ /Ca 2þ -exchanged bentonite (Manjanna et al, 2009;Melkior et al, 2009) and data obtained with clay-rocks that showed evidence of significant alteration (Cavé et al, 2009) or for which the clay mineralogy was not fully characterized (Cole et al, 2000;Hendry et al, 2009;Barbour et al, 2012). The studies included in the database are listed in Table 6.1 (for bentonite) and Table 6.2 (for clay-rocks).…”
Section: Compilation Of Diffusion Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that focused on very low solid-water ratios (Nakashima et al, 1999), that used high concentrations of the diffusing species (Nakashima, 2002(Nakashima, , 2003bLoomer et al, 2013), or that studied the codiffusion of multiple species (De Soto et al, 2012) were excluded, as were data obtained with bentonites other than Na þ -, Ca 2þ -, or Na þ /Ca 2þ -exchanged bentonite (Manjanna et al, 2009;Melkior et al, 2009) and data obtained with clay-rocks that showed evidence of significant alteration (Cavé et al, 2009) or for which the clay mineralogy was not fully characterized (Cole et al, 2000;Hendry et al, 2009;Barbour et al, 2012). The studies included in the database are listed in Table 6.1 (for bentonite) and Table 6.2 (for clay-rocks).…”
Section: Compilation Of Diffusion Datamentioning
confidence: 99%
“…In porous media with such low k values, at hydraulic pressure gradients representative of subsurface conditions, molecular diffusion is an important mass transfer mechanism on length scales up to hundreds of meters and millions of years, with implications in the isolation of landfills and contaminated sites (Johnson et al, 1989;Jo et al, 2006;Lange et al, 2009;De Soto et al, 2012), the persistence of dense nonaqueous-phase liquids (DNAPL) in contaminated aquifers (Parker et al, 2004;Chapman and Parker, 2005), the distribution of inert tracers in clay formations (Patriarche et al, 2004b;Lavastre et al, 2005;Mazurek et al, 2011), and the geologic storage of CO 2 (Ketzer et al, 2005;Gherardi et al, 2007) and high-level radioactive waste (HLRW) . Because of the important role of molecular diffusion in clay materials, extensive experimental efforts have aimed to characterize the associated diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic conductivity (HC) of this clay is less than 1610 À9 m/s at the optimum density (Proctor dry density) of 1.85 g/cm 3 (the highest permeability allowed by the Spanish and EU regulations for liner shields; Real Decreto 1481/2001). This material is composed of illite (33%), smectite (12%), kaolinite (7%), calcite (11%), dolomite (5%), quartz (30%), albite (1%) and pyrite (De Soto et al, 2012).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…Leachates are defined as the aqueous effluents generated from the rainwater percolation through the wastes, the biochemical processes in the waste cells and the inherent water content of the wastes themselves (Renou et al, 2008). The main biogeochemical and transport processes in landfill areas involving the interaction between the leachates and clay liners are solute diffusion (Foged & Baumann, 1999;Rosanne et al, 2003;Appelo et al, 2010;De Soto et al, 2012;Shackelford & Moore, 2013), anion exclusion (Bradbury & Baeyens, 2003;Molera et al, 2003;Montes et al, 2005;Van Loon et al, 2007;Kang & Shackelford, 2010;Ruiz et al, 2012), cation exchange processes (Christensen et al, 2000;Thornton et al, 2000;Malusis et al, 2003;Pivato & Raga, 2006;Birgersson & Karnland, 2009;Regadío et al, 2012), biologically mediated redox reactions (Christensen et al, 2000;Van Breukelen, 2003;Thabet et al, 2009;Li et al, 2011) and mineral precipitation/dissolution, which can modify the barrier porosity (VanGulck & Rowe, 2004a, b;Castelló et al, 2008). All these mechanisms affect the confinement properties of the clay barriers and should therefore be studied in detail.…”
mentioning
confidence: 99%
“…Sometimes, some of the leachate may percolate through the soil to contaminate the groundwater, particularly in an unlined landfill (Mor et al, 2006). Advection and diffusion are also transport processes responsible for contaminant mixing and movement of leachate into groundwater (De Soto et al, 2012).…”
mentioning
confidence: 99%